Cardiac sodium channel blockade after an intentional ingestion of lacosamide, cyclobenzaprine, and levetiracetam: Case report. (July 2015) - Chua-Tuan, Jenny L.; Cao, Dazhe; Iwanicki, Janetta L.; Hoyte, Christopher O.
Abstract: Context . Lacosamide treats partial seizures by enhancing slow inactivation of voltage-gated sodium channels. The described cardiac toxicity of lacosamide in the literature to date includes atrioventricular blockade (PR prolongation), atrial flutter, atrial fibrillation, sinus pauses, ventricular tachycardia and a single cardiac arrest. We report a second case of cardiac arrest following an intentional lacosamide overdose. Case details . A 16 year-old female with a seizure disorder was found unresponsive in pulseless ventricular tachycardia after intentionally ingesting 4.5 g (76 mg/kg) lacosamide, 120 mg (2 mg/kg) cyclobenzaprine and an unknown amount of levetiracetam. Exact time of ingestion was unknown. Her initial electrocardiogram (ECG) demonstrated sinus tachycardia at 139 beats per minute, QRS duration 112 ms, and terminal R-wave in lead aVR > 3 mm. Despite treatment with 150 mEq of sodium bicarbonate, she had persistent EKG findings eight hours after presentation. Her serum lacosamide concentration nine hours after presentation was elevated at 22.8 μg/mL, while serum cyclobenzaprine concentration was 16 ng/mL (therapeutic: 10–30 ng/mL), and serum levetiracetam concentration was 22.7 μg/mL (therapeutic: 12–46 μg/mL). On hospital day three, ECG demonstrated resolution of the terminal R-wave with QRS of 78 ms. The patient recovered without physical or neurologic sequelae. Discussion . The patient's lacosamide, cyclobenzaprine and levetiracetam overdose was associated with QRS prolongation and terminal right axis deviation – suggesting sodium channel blockade as a likely etiology for her cardiac arrest. Cyclobenzaprine has potential for sodium channel blockade and ventricular dysrhthmias although cardiac toxicity due to cyclobenzaprine alone is rare. The combination of cyclobenzaprine with lacosamide may have resulted in cardiovascular collapse. In conclusion, overdose of lacosamide combined with therapeutic concentrations of sodium channel blocking xenobiotics may cause cardiac conduction delays and cardiac arrest.